The reproduction in women affected by Cooley disease - Carlo Pafumi; Vito Leanza; Luana Coco; Stefania Vizzini; Lilliana Ciotta; Alessandra Messina; Gianluca Leanza; Giuseppe Zarbo; Alfio D'Agati; Marco Antonio Palumbo; Alessandra Iemmola; Ferdinando Antonio Gulino; et al. (Hematology Reports, 2011)
The health background management and outcomes of 5 pregnancies in 4 women affected by Cooley Disease, from Paediatric Institute of Catania University, are described, considering the preconceptual guidances and cares for such patients. These patients were selected among a group of 100 thalassemic women divided into three subgroups, according to their first and successive menstruation characteristics: i) patients with primitive amenorrhoea, ii) patients with secondary amenorrhoea and iii) patients with normal menstruation. Only one woman, affected by primitive amenorrhoea, needed the induction of ovulation. A precise and detailed pre-pregnancy assessment was effected before each conception. This was constituted by a series of essays, including checks for diabetes and hypothyroidism, for B and C hepatitis and for blood group antibodies. Moreover were evaluated: cardiac function, rubella immunity and transaminases. Other pregnancy monitoring, and cares during labour and delivery were effected according to usual obstetrics practice. All the women were in labour when she were 38 week pregnant, and the outcome were five healthy babies born at term, weighting between 2600 and 3200gs. The only complication was the Caesarean section. The improvements of current treatments, especially in the management of iron deposits, the prolongation of survival rate, will result in a continuous increase of pregnancies in thalassemic women. Pregnancy is now a real possibility for women affected by such disease. We are furthermore studying the possibility to collect the fetus' umbilical cord blood, after the delivery, to attempt eterologus transplantation to his mother trying to get a complete marrow reconstitution.